The Cove - Rash, Ron, 1953- (HarperCollins Publishers, 2012)
Living deep within a cove in the Appalachians of North Carolina during World War I, Laurel Shelton finally finds the happiness she deserves in Walter, a mysterious stranger who is mute, but their love cannot protect them from a devastating secret.